2007
DOI: 10.4081/ijas.2007.1s.421
|View full text |Cite
|
Sign up to set email alerts
|

Use of near infrared spectroscopy for assessment of beef quality traits

Abstract: Chemical and physical traits and fatty acid composition of meat samples from 148 Piemontese beef samples were predicted by near infrared spectroscopy. Coefficients of determination in calibration (R2) ranged between 0.44 and 0.99 for chemical composition and between 0.02 and 0.98 for fatty acid (FA) profile, being in general more accurate for the major FA. The calibration results gave inaccurate prediction for cholesterol and collagen content and for most physical traits, such as Warner-Bratzler shear force, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 9 publications
4
14
1
5
Order By: Relevance
“…The fluorescence measurement can be considered as a surface measurement and the grinding of the sample can permit to record a fluorescence signal that is more representative of the sample. NIR spectroscopy is undoubtedly the most used method for predicting total lipids in beef, some studies after cross-validation reported a R 2 cv and RPD higher than 0.9 and 3.5 respectively (De Marchi, Berzaghi, Boukha,Mirisola, & Gallo, 2007;Mourot et al, 2015;Tøgersen, Arnesen, Nilsen, & Hildrum, 2003) suggesting that this spectral method presented probably a higher accuracy to predict total lipids in beef.…”
Section: Total Lipids and Fatty Acids Prediction In Meatmentioning
confidence: 96%
“…The fluorescence measurement can be considered as a surface measurement and the grinding of the sample can permit to record a fluorescence signal that is more representative of the sample. NIR spectroscopy is undoubtedly the most used method for predicting total lipids in beef, some studies after cross-validation reported a R 2 cv and RPD higher than 0.9 and 3.5 respectively (De Marchi, Berzaghi, Boukha,Mirisola, & Gallo, 2007;Mourot et al, 2015;Tøgersen, Arnesen, Nilsen, & Hildrum, 2003) suggesting that this spectral method presented probably a higher accuracy to predict total lipids in beef.…”
Section: Total Lipids and Fatty Acids Prediction In Meatmentioning
confidence: 96%
“…Among physical traits, considerable attention has been paid to the prediction of pH (Prieto et al, 2008), color (Cecchinato et al, 2011;Leroy et al, 2003;Liu et al, 2003;Prieto et al, 2008), water holding capacity (De Marchi et al, 2007;Leroy et al, 2003;Ripoll, Albertí, Panea, Olleta, & Sañudo, 2008), and tenderness Liu et al, 2003;Prieto et al, 2008). Nevertheless, the results are not completely satisfactory and they are contradictory for several attributes.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, this technology is used both for research and routine quality assessment (Alomar, Gallo, Castañeda, & Fuchslocher, 2003;Cozzolino & Murray, 2002;Prieto, Andrés, Giráldez, Mantecón, & Lavín, 2006). Infrared spectroscopy has demonstrated its potential to predict chemical composition (Alomar et al, 2003;De Marchi, Berzaghi, Boukha, Mirisola, & Gallo, 2007;Prieto et al, 2006) and some physical traits (Cecchinato, De Marchi, Penasa, Albera, & Bittante, 2011;Liu et al, 2003;Prieto, Andrés, Giráldez, Mantecón, & Lavín, 2008) of beef.…”
Section: Introductionmentioning
confidence: 99%
“…reported similar calibration statistics for C14:0, whereas C16:1 n 7 and C18:1 n 7 were not reported. The better predictions obtained for the most abundant individual FA and FA groups indicate that near infrared spectroscopy performed better with abundant compounds or with a FA concentration > 0.05 g kg −1 dry matter …”
Section: Resultsmentioning
confidence: 95%